Improving Energy Security by Increasing the Efficiency of System Gathering Production Oil and Gas Well - Aghadiyeva, T.A. (Herald of Azerbaijan Engineering Academy, 2024)
The general strategy is shown of management by economic on based the increasingly full application of intensive methods of management. The needs are analyzed of the volume of compressed gas for the normal and continuous operation of oil and gas wells, which are determined by the number of simultaneously operating compressors. It has been established that technological facilities, from the formation to the supply of associated petroleum gas to the intake of the gas-lift compressor system are a single, multi-link, inseparable system.